The Effectiveness of the Role of the Village Government in Suppressing Dropout Rates in Pattongko Village - Sofyang Sofyang; Syamsiah Hasyim (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Education is essentially an effort to facilitate students to be able to solve problems in life that they will face in the future. This research aims to determine the effectiveness of the role of the village government in reducing the dropout rate in Pattongko Village, Sinjai Tengah District, Sinjai Regency, and the factors that cause school dropout. This research uses qualitative research. The data collection techniques used were interviews, observation, and documentation. The data analysis technique used is data collection, data reduction, data presentation, decision making (verification). The results of this study state that the effectiveness of the role of the village government in suppressing the dropout rate in Pattongko Village, Sinjai Regency, related to its role as a motivator, facilitator, and mobilizer basically tends to be effective, this can be seen from the decrease in the dropout rate every year. this is due to the concern of the local government, especially the village government together with parents and the community. The factors causing dropping out of school in Pattongko Village in this study consisted of four factors, namely the Child itself, the Economic Condition, the distance between the house and the school which was far away, and the parents' lack of understanding of the importance of education.